2014
DOI: 10.5901/mjss.2014.v5n2p403
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education in South Africa

Abstract: This paper discusses entrepreneurship education in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 41 publications
5
65
0
1
Order By: Relevance
“…A major assumption in these developments is that entrepreneurship education increases students' career prospects and employability, either through enabling them to become selfemployed persons or through increasing their potential value as more enterprising employees . Consequently, lots of efforts are being put into advancement of entrepreneurship education in formal school curriculum (Chimucheka, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A major assumption in these developments is that entrepreneurship education increases students' career prospects and employability, either through enabling them to become selfemployed persons or through increasing their potential value as more enterprising employees . Consequently, lots of efforts are being put into advancement of entrepreneurship education in formal school curriculum (Chimucheka, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The author has recommended the roll out of tailor-made training and mentorship programmes. Chimucheka (2014) has found that start-up SMMEs in the footwear and textile sector often struggle to secure loans that are needed for business operation. The author has pointed out that start-up SMMEs in the footwear and textile industry often fail to order large quantities of merchandise from wholesale suppliers due to difficulty in borrowing money from loan providers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pendapat yang sama dikatakan oleh (Florea dan Florea, 2013), yang menjelaskan bahwa program pendidikan dan pelatihan kewirausahaan telah memberi kontribusi terhadap pembangunan ekonomi. Demikian juga dengan penelitian (Chimucheka, T, 2014) menunjukkan terdapat hubungan kewirausahaan dengan pendidikan untuk meningkatkan usaha kecil dan peranan pendidikan kewirausahaan pada negara berkembang untuk mengkonstruksi program kewirausahaan (Mastura, Jaafar, et al 2008;Richard, Mandel, and Erik Noyes, 2016;Farhangmehr et. al, 2016).…”
Section: Kajian Teoriunclassified